Marketing Mix Strategy of Culinary MSMEs in South Tangerang City During the Covid-19 Pandemic - Syamruddin Syamruddin; Ruknan Ruknan; Oki Iqbal Khair (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
This study aims to determine the development of Culinary SMEs in South Tangerang City. In addition to knowing the marketing mix strategy in the management of Culinary MSMEs in South Tangerang City during the Covid-19 Pandemic. This research method is qualitative. The research was conducted on Culinary SMEs in South Tangerang City. Determination of the informant as the selected data source using purposive sampling technique. Collecting data using observation, interview and documentation techniques. The validity of the data is obtained through credibility, transferability, dependability, and confirmatory. Qualitative data analysis: data reduction, data exposure, and drawing conclusions. The results showed that: 1) The number of Culinary MSMEs in South Tangerang City in 2021 amounted to 28,036, with details: Pamulang District 5.552, Setu District 2,084, Ciputat District 4,235, Ciputat Timur District 3,754, Serpong District 4,274, North Serpong District 2,911, and Pondok Aren District 5,226. The number of Culinary MSME workers in South Tangerang City is very large, namely 51,095 people. Then the total turnover of Rp. 3,933,700,000,000,-. 2) The marketing mix strategy carried out by Culinary MSMEs in South Tangerang City during the Covid-19 Pandemic, namely: in terms of products, in addition to offering new products, innovations are also made to existing products so that they are more attractive to consumers; in terms of price, many Culinary MSME managers make adjustments; in terms of promotion, in addition to giving discounts, promotions are carried out through word of mouth, networking for the Culinary MSME community and online; from the place side, from the place side, the sales system carried out during the Covid-19 pandemic is more limited in nature, the Culinary MSME managers use more facilities through the online system.